2009
DOI: 10.1074/jbc.m109.022863
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-type Phosphoenolpyruvate Carboxylase (PEPC) Functions as a Catalytic and Regulatory Subunit of the Novel Class-2 PEPC Complex of Vascular Plants

Abstract: Phosphoenolpyruvate carboxylase (PEPC) is a tightly regulated anaplerotic enzyme situated at a major branch point of the plant C metabolism. Two distinct oligomeric classes of PEPC occur in the triglyceride-rich endosperm of developing castor oil seeds (COS). Class-1 PEPC is a typical homotetramer composed of identical 107-kDa plant-type PEPC (PTPC) subunits (encoded by RcPpc3), whereas the novel Class-2 PEPC 910-kDa hetero-octameric complex arises from a tight interaction between Class-1 PEPC and distantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
88
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 31 publications
6
88
0
Order By: Relevance
“…In plants, multisubunit composition and changes in oligomeric assembly, depending on the tissue and the metabolic situation, are properties of important glycolytic and TCA cycle enzymes such as pyruvate kinase, NAD-isocitrate dehydrogenase, and PP i -dependent phosphofructokinase and phosphoenolpyruvate carboxylase (35)(36)(37)(38)(39). These characteristics represent a mechanism of allosteric regulation of enzymes of central metabolic pathways (40).…”
Section: Is the Formation Of Alternative Oligomeric Forms A Fine-tunimentioning
confidence: 99%
“…In plants, multisubunit composition and changes in oligomeric assembly, depending on the tissue and the metabolic situation, are properties of important glycolytic and TCA cycle enzymes such as pyruvate kinase, NAD-isocitrate dehydrogenase, and PP i -dependent phosphofructokinase and phosphoenolpyruvate carboxylase (35)(36)(37)(38)(39). These characteristics represent a mechanism of allosteric regulation of enzymes of central metabolic pathways (40).…”
Section: Is the Formation Of Alternative Oligomeric Forms A Fine-tunimentioning
confidence: 99%
“…In contrast, BTPC genes encode larger 116-to 118-kD polypeptides owing to a unique intrinsically disordered region that mediates BTPC's tight interaction with coexpressed PTPC subunits. This association results in the formation of unusual Class-2 PEPC heterooctameric complexes that are largely desensitized to allosteric effectors and that dynamically associate with the surface of mitochondria in vivo (O'Leary et al, 2009(O'Leary et al, , 2011aIgawa et al, 2010;Park et al, 2012).…”
mentioning
confidence: 99%
“…Class-1 PEPCs also fulfill a wide range of crucial nonphotosynthetic functions, particularly the anaplerotic replenishment of tricarboxylic acid cycle intermediates consumed during biosynthesis (O'Leary et al, 2011a). Class-1 PEPCs are subject to a complex set of posttranslational controls including allosteric effectors, covalent modification via phosphorylation or monoubiquitination, and protein-protein interactions (Uhrig et al, 2008;O'Leary et al, 2009O'Leary et al, , 2011aO'Leary et al, , 2011b.…”
mentioning
confidence: 99%
“…Whereas most PEPCs exist as homotetramers (class 1 PEPC) (1), bacterial-type PEPCs associate with plant-type isozymes to form a heteromeric complex (class 2 PEPC) in unicellular green algae (11) and castor oilseeds (12). It has been recently shown that Class-2 PEPC is composed of four each of the bacterial-and plant-type isozymes (13).…”
mentioning
confidence: 99%